Impact of Mindfulness-Based Stress Reduction on Anxiety Levels in Healthcare Professionals: A Comparative Study - Dr. Payal Aniket Pawar; Dr. Vilas Dattatraya Chvan; Dr. Anup Manaklal Rathi; Dr. Mayur Kiran Muthe (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Healthcare professionals frequently encounter high levels of stress and anxiety, which can adversely affect their health and job performance. Mindfulness-Based Stress Reduction (MBSR) has been identified as a potential intervention to mitigate these effects. Objective: This study aimed to evaluate the efficacy of an 8-week MBSR program in reducing anxiety levels among healthcare professionals compared to a control group receiving no intervention. Methods: A total of 140 healthcare workers from a single tertiary care center were randomly assigned to either the MBSR group or a control group. The MBSR group participated in an 8-week program consisting of guided mindfulness exercises, yoga, and meditation. Anxiety levels were measured using the Generalized Anxiety Disorder 7-item scale (GAD-7) at baseline and post-intervention. Results: Baseline anxiety levels were comparable between the two groups (MBSR: 14.3 ± 2.7; Control: 14.1 ± 2.8). Post-intervention results showed a significant reduction in anxiety scores in the MBSR group (10.4 ± 2.2) compared to the control group (13.9 ± 2.6), with a p-value < 0.001. The effect size of the intervention was significant, indicating a robust treatment effect. Conclusion: The findings suggest that MBSR is an effective intervention for reducing anxiety among healthcare professionals. The significant decrease in anxiety scores post-intervention highlights the potential of MBSR to enhance mental health and stress management in high-pressure medical environments.